2015
DOI: 10.1111/jfq.12185
|View full text |Cite
|
Sign up to set email alerts
|

Meat Tenderness Genetic and Genomic Variation Sources in Commercial Beef Cattle

Abstract: To assess genetic group (GGR; Bos indicus [Bi], Bos taurus [Bt] and crosses [BtxBi]) and to confirm the calpain (CAPN316 and CAPN4751) and calpastatin (CAST-T1) single nucleotide polymorphism (SNP) effects on Warner-Bratzler shear force (WBSF), 196 animals under commercial conditions were analyzed. A model was fitted including the effect of GGR and considering residuals as adjusted WBSF (aWBSF). Another model was fitted to evaluate the SNP effect on aWBSF. Allele substitution effect (α) and combined favorable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…A previous study has been reported that the 5'UTR region of CAPN1 gene was polymorphic in Bali cattle nevertheless quite low nucleotide diversities (Pi) of 0.00632 (Jakaria et al 2020). Previously, the role of CAPN gene has been reported that the u-calpain is the enzyme proteolysis, contributes to meat tenderness (Avilés et al 2013;Lozano et al 2016). The coding region of CAPN1 gene polymorphisms association with meat quality has been widely reported in cattle.…”
Section: Polymorphisms Of Snp G232 G>t 5'utr Regionmentioning
confidence: 99%
“…A previous study has been reported that the 5'UTR region of CAPN1 gene was polymorphic in Bali cattle nevertheless quite low nucleotide diversities (Pi) of 0.00632 (Jakaria et al 2020). Previously, the role of CAPN gene has been reported that the u-calpain is the enzyme proteolysis, contributes to meat tenderness (Avilés et al 2013;Lozano et al 2016). The coding region of CAPN1 gene polymorphisms association with meat quality has been widely reported in cattle.…”
Section: Polymorphisms Of Snp G232 G>t 5'utr Regionmentioning
confidence: 99%
“…The calpain/calpastatin system consists of two calcium-requiring proteases known as μ -calpain (CAPN1) and m-calpain (CAPN2) and its inhibitor, calpastatin (CAST), with both playing an essential role in skeletal muscle apoptosis, protein turnover, myogenesis and metabolism (Campbell & Davies 2012). Recently, the calpain/calpastatin proteolytic systems have been investigated at mRNA level (Rubio Lozano et al 2016). However, the mRNA expression of genes does not always explain the differences in myofibrillar proteolysis in skeletal muscle of Bos taurus and Bos indicus cattle (Giusti et al 2013).…”
Section: Introductionmentioning
confidence: 99%